2002
DOI: 10.1046/j.1365-2184.2002.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative positions of kinetoplasts in Trypanosoma musculi and Trypanosoma lewisi during development in vitro

Abstract: The development of Trypanosoma musculi and Trypanosoma lewisi were studied in vitro in the presence of adherent splenic cells. Both parasites developed only when attached by their flagellar tips to adherent splenic cells. During the proliferation of T. musculi, the kinetoplast migrated towards the nucleus, and once in the vicinity of the nucleus, the nuclear division was triggered. The kinetoplast of T. lewisi did not migrate towards the nucleus, but remained at its original location. The nucleus and kinetopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Epimastigote stages with multiple divisions forming rosette shaped structures were described in early studies [13,16,17], while the expected proliferation in trypomastigotes was rarely observed and it was suggested that they may require transformation to epimastigotes [1]. In a later study, proliferation of trypomastigotes was observed when it was cultured in vitro [18]. However, detailed information regarding the cell cycle events was not provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epimastigote stages with multiple divisions forming rosette shaped structures were described in early studies [13,16,17], while the expected proliferation in trypomastigotes was rarely observed and it was suggested that they may require transformation to epimastigotes [1]. In a later study, proliferation of trypomastigotes was observed when it was cultured in vitro [18]. However, detailed information regarding the cell cycle events was not provided.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have cultured Herpetosoma trypanosomes in association with various mammalian cell lines [12][13][14][15]. In the early studies, T. lewisi had been maintained continuously [11] and morphological polymorphism was observed during in vitro cultivation [16][17][18]. However, there has been no systematic analysis, to date, that resolves these morphological cell types and relates them to the corresponding cell cycle events.…”
Section: Introductionmentioning
confidence: 99%